Analisis Efisiensi Teknis Produksi Cabai Tiung di Kabupaten Tabalong Menggunakan Stochastic Frontier Analysis - Rusmiliani Olfah; Nuri Dewi Yanti; Hamdani Hamdani (Jurnal Agrosains dan Teknologi, 2026)
Tiung chili is a superior local variety in Tabalong Regency with high economic value but fluctuating productivity, with farming systems generally managed traditionally with suboptimal input utilization. This study analyzes production factors affecting output, measures farmers’ technical efficiency levels, and identifies factors influencing technical inefficiency in Tiung chili production. Primary data were collected from 60 farmer respondents through surveys and structured interviews during the 2024 growing season. Analysis employed Cobb-Douglas production function with Stochastic Frontier Analysis approach estimated using Maximum Likelihood Estimation through Frontier 4.1 software. Land area has a significant positive effect (β = 0.845; t = 4.723), while pesticides have a significant negative effect (β = -0.123; t = -2.550). Seeds, labor, and fertilizers have no significant effect. The average technical efficiency is 0.772 with most farmers in the 0.8-0.9 interval (53.33%). Gamma value of 0.886 indicates that 88.6% of production variation is caused by technical inefficiency. Age, education, farming experience, and training have no significant effect on technical inefficiency. There is an opportunity to increase output by 29.5% without additional inputs through improved farm management, indicating that productivity improvement is primarily limited by management factors rather than external shocks.